2022
DOI: 10.1101/2022.01.28.478242
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic changes to signal allocation rules in response to variable social environments in house mice

Abstract: Male house mice use metabolically costly urine marks in intrasexual competition and mate attraction. Given the high costs of signaling and the depletable nature of urine reserves, males should dynamically modulate signal allocation as the social landscape is updated with new information. We investigate which aspects of male urine marking behavior are static or dynamic in light of changing social environments. To do this, we use thermal imaging to capture spatiotemporal data of urine deposition decisions. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 92 publications
1
12
2
Order By: Relevance
“…Males were categorized as either low or high-marking individuals, based on whether their total number of urine deposition events fell below or above the median number of marks ( Figures 3A & S1A ). This categorization is supported by our prior work, which shows that initial mark investment predicts marking levels days later ( Figure S1 ; 48). In other words, males that are low or high-marking adhere to their respective marking groups days after an aggressive contest (48).…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…Males were categorized as either low or high-marking individuals, based on whether their total number of urine deposition events fell below or above the median number of marks ( Figures 3A & S1A ). This categorization is supported by our prior work, which shows that initial mark investment predicts marking levels days later ( Figure S1 ; 48). In other words, males that are low or high-marking adhere to their respective marking groups days after an aggressive contest (48).…”
Section: Resultssupporting
confidence: 80%
“…Previous work described males reducing their scent marking after losing (41). Indeed, in the trials reported here, we found that high-marking males dramatically reduce their marking efforts after losing (48). However, this scenario does not readily explain the observed patterns among winning males that continue to mark infrequently.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations